Factors Associated with the Uptake of Family Planning Services by Women Attending Maternal Clinic at Rongo Sub-County Hospital in Migori County, Kenya - Otieno, Churchill Ochieng (JOOUST, 2023)
Family planning services play a crucial role in improving the health of women and children in developing countries by providing safe and effective methods to reduce the number of births and high-risk pregnancies. Despite efforts to promote fertility control, a significant proportion of women in the reproductive age group (15-49 years) do not utilize family planning services, either due to non-use or ineffective use. In Kenya, the total fertility rate remains high at 4.6%, while the contraceptive prevalence rate (CPR) and unmet need for family planning stand at 46% and 24%, respectively (DHS 2022). However, in Migori County, the modern contraceptive uptake rate is 60.3%. This study aimed to examine the factors associated with the uptake of family planning services among 145 women attending maternal clinic at Rongo Sub-County Hospital in Migori County, Kenya. The research sought to determine the uptake of family planning services and identify socioeconomic and health facility factors influencing their utilization. A cross-sectional study design was employed, and participants were selected using systematic random sampling. Data was collected through questionnaires, interviews, and focus group discussions, with both primary and secondary sources utilized. Quantitative data analysis involved descriptive and inferential statistics, while qualitative data was organized into themes and patterns. The results revealed that 68.3% (99) of women in Rongo Sub-County utilized family planning services. The study also observed a significant association between culture, religious affiliation, and the utilization of family planning services (OR=5.413, p=0.033). Additionally, the method of family planning adopted was also found to influence its usage (AOR=1.74, p=0.051, 95% CI=-0.996-32.626). Women were less likely to use family planning services when facilities lacked skilled health providers (AOR=-2.26, p=0.003, 95%CI=-3.02 0.463). These findings emphasize the importance of public sensitization, involving both women and men, to increase the acceptability of modern family planning services. Adequate staffing of health facilities and comprehensive counselling services are also recommended to ensure the proper administration of family planning services.
Keywords: Family Planning Services